"Composición química, degradabilidad y cinetica ruminal in-situ del matarraton (gliricidia sepium) en diferentes periodos de corte". - Montecé Loor, Jennifer Janina (2019)
The research was carried out in the Experimental Farm "La María" Rumiology and Nutritional Metabolism Laboratory (RUMEN) of the State Technical University of Quevedo (UTEQ), Faculty of Animal Sciences (FCP), located at km 71/2 via Quevedo - El Empalme, Province of Los Ríos, at 01º 06` 30 "South latitude and 79º 29` 30" West latitude and at an altitude of 73 masl. The chemical composition, degradability and ruminal kinetics in situ (MS, MO, PC, NDF and FDA) of the marathon (Gliricidia sepium) were evaluated in different cutting periods (30, 45, 60, 75, 90 and 105 days). A completely randomized design (DCA) was applied with four repetitions and for the differences between Tukey means (P<0,05). The MS; MO and MI were not affected (P<0,05) by the cut periods evaluated. However, the highest percentages (P<0,05) of PC and NDF were recorded at 30 and 60 days of regrowth (23,07 and 52,93%, respectively). The highest (P<0,05) in situ degradability of MS was obtained at 75 and 105 days of the cut-off period, at 6 and 24 hours of incubation (98,12 and 99,46%). The highest degradability (P<0,05) of MO was recorded at 30 days of the cut-off period at 96 hours of incubation (96,23%). However, the highest values for in situ degradability of the NDF were recorded in the cut-off periods of 30 and 45 days, at 96 hours of incubation (87,38 and 93,79%), meanwhile, the FDA at 45 days, at 96 hours of incubation (73,57%). The highest (P<0,05) Effective Degradability (SD: 2; 5 and 8% / hour) of the MS was obtained at 75 and 105 days. While for the MO at 30 days of the cut-off period (93,66; 90,83; 88,18%, respectively). But the highest values for the NDF and FDA were recorded at 75 days of the cut-off period (78,40; 75,01; 71,91 – 58,47; 55,67; 53,23%, respectively). Key words: Ruminal kinetics, forages, ruminants, nutrition, feeding.